Peran Bela Negara dalam Meningkatkan Kewaspadaan Nasional dan Implementasi Otonomi Khusus Aceh - Khalisni, Khalisni; Fajri, Nurul; Sari, Novita (Journal of Political Sphere, 2023)
This research aims to analyze the role of National Defense in enhancing national vigilance and implementing Special Autonomy in Aceh. In the context of Indonesia's political and security dynamics, efforts to maintain national integrity and increase national vigilance are of paramount importance. The Special Autonomy granted to Aceh as a form of special authority in the province is also a crucial factor to be considered in the context of national security policy development. This research utilizes a qualitative descriptive method. Data for the study were obtained through literature review, national and regional policy documents related to Aceh. The study begins by elucidating the concepts of National Defense and national vigilance. Furthermore, the research discusses the implementation of Special Autonomy in Aceh and the role played by the local government in the context of national security policy development. The findings of this research indicate that the role of National Defense has a significant impact on enhancing national vigilance at the local level, including in the province of Aceh with its Special Autonomy status. Through active participation of the community and a strong role of the local government, the implementation of Special Autonomy in Aceh can contribute positively to the development of a more holistic national security policy. By understanding the role of National Defense, the Aceh local government can design programs that involve all components of society in safeguarding national security and strengthening national vigilance across Indonesia.